2SPD-035 Biological therapies effectiveness comparison for patients with severe–moderate psoriasis. (14th March 2021) - Cordero, J; Castillo-Martin, C; Fernández-González, M; Martinez-Suárez, A; Rendón-Delope, L
Abstract : Background and importance: The current treatment of psoriasis aims to maintain control of skin involvement and systemic inflammation, as well as prevention of the onset or progression of systemic comorbidities and depends on the severity of the disease. Aim and objectives: The objective was to perform a comparison of the most common therapies in the treatment of patients with moderate to severe psoriasis used as an alternative to tumour necrosis factor-alpha inhibitors (anti-TNFα ). Material and methods: The therapies included were found after a systematic search performed in Pubmed. The analysis included randomised, double-blind, phase III controlled trials, non-TNF targeted therapies and PASI75 measurement after 12–16 weeks of treatment. The analysis was performed using the R software to estimate Bayesian statistics, with risankizumab taken as a reference for the comparison. A delta value of 14%, as provided by the regulatory agencies FDA and EMA, was used to determine the margin (maximum acceptable difference as a non-inferiority criteria), and the average PASI75 response was set at 12 weeks of risankizumab at 79% (95% CI 74 to 84) (ULTIMMA1 and ULTIMA2 trials). To establish therapeutic positioning, the ATE (equivalent therapeutic alternatives in Spanish) guide criteria were applied. Results: 20 clinical trials were included, containing the following drugs: risankizumab, tildrakizumab, guselkumab, brodalumab, ixekizumab, secukinumab and ustekinumab. An equivalence margin expressed as odds ratio (OR) was established from 0.46 to 2.11. The results of the different treatments against risankizumab (reference) expressed as OR (95% CI) were: 1 (0.89 to 1.21) for brodalumab, 1.39 (1.13 to 1.94) for ixekizumab, 0.84 (0.0.68 to 1.13) for secukinumab, 1.21 (0.79 to 2.15) for guselkumab, 0.35 (0.28 to 0.41)for tildrakizumab and 0.47 (0.3 to 0.75) for ustekinumab. Conclusion and relevance: Brodalumab and secukinumab were identified as risankizumab equivalent. For ixekizumab, it can be considered as a clinical equivalent, even though statistically significant differences (ixekizumab > risankizumab) were observed but they were clinically irrelevant. In the case of guselkumab, it can be labelled as a possible clinical equivalent as the 95% CI exceeded the equivalence margin, but it is unclear if such a difference exists (being statistically non-significant). Ustekinumab and tildrakizumab cannot be considered equivalent; the former had likely relevant and statistically significant differences (50% of its 95% CI was outside the equivalence range), and tildrakizumab had clearly relevant and statistically significant differences as all of its 95% CI was outside the equivalence range. References and/or acknowledgements: Conflict of interest: No conflict of interest